News about the doctorate in Law in Salamanca in the early 20th century - Torijano Pérez, Eugenia (CIAN-Revista de Historia de las Universidades, 2022)
The text deals with the intention of the Counts of Val and the Bishop of Salamanca to provide doctorate chairs in Law linked to the University of Salamanca under the supervision of a board created in last wills in Salamanca. This intention, very difficult to fulfill, was echoed in the Salamanca press and gave rise to a heated debate between the two social and political factions in which Salamanca society and Spanish society in general were divided.